Serum matrix metalloproteinase-2,9 activity, galectin-3 and systemic inflammation in patients with postinfarction heart failure with preserved ejection fraction. - O. Kuryata; A. Zabida; O. Sirenko (Medičnì Perspektivi)
The available data suggest that heart failure (HF) after myocardial infarction (MI) is a very frequent event. Recent meta-analysis showed that restrictive mitral filling pattern, the most severe form of diastolic dysfunction, was presented in approximately 10% of the patients with preserved ejection fraction. In addition, restrictive pattern was associated with poor outcome. However, the true prevalence and relevance of diastolic dysfunction after MI remains to be elucidated. Objective: study was designed to evaluate the serum level of MMP-2,9, galactin-3 and C-reactive protein (C-RP) in postinfarction heart failure with preserved ejection fraction (HFpEF) patients. Methods: We divided all included patients into two main groups: 1st group – 20 patients with HFpEF and history of myocardial infarction. 2nd group – 18 patients with HFpEF and stable angina. Standard laboratory blood tests for erythrocyte sedimentation rate (ESR), C-RP, haematological parameters, lipid profile, glucose, renal and liver function tests were performed and calculated body mass index (BMI) for all patients. MMP activity assay and galectin-3 serum level was detected for all patients. Results: It was established significant differences between study groups in MMP-2, MMP-9 levels. Particularly, patients with HFpEF with MI in anamnesis had significantly higher MMP-2, MMP-9 levels on 21.8% and 20.7% respectively. The C-RP and leucocytes levels were significantly higher in 1st group pts. Significant differences in MMP-2, MMP-9 were established in 1st group patients in different age groups (p<0.05) (tab. 3). The MMP 2 level was positively correlated with MMP 9 level (R=0.73, p<0.05), the MMP 9 level – with age (R=0.68, p<0.05). There were no significant differences between galectin-3 level in study group. But we estimated significant differences in galectin-3 level between 1st and 2nd subgroups (p<0.05). Conclusion: Serum MMP-2, MMP-9, CRP and galactin-3 were significantly increased in pts with postinfarction heart failure with preserved ejection fraction compare to pts without myocardial infarction in anamnesis.